MORPHOPHYSIOLOGICAL AND GENETIC ADAPTATIONS OF PLANTS TO DROUGHT STRESS: https://doi.org/10.5281/zenodo.15352395 - Kushanov , F.N; Ernazarova , D.Q; Mirzosharipova , M.S (International scientific and practical conference, 2025)
This article discusses abiotic stress factors affecting plants, particularly morphophysiological adaptation strategies to drought and their genetic basis. Under drought conditions, plants exhibit flexibility by reducing water loss, deepening root systems, and altering leaf structures. The article also explores genetic mechanisms of drought resistance and their expression, analyzing how plants combat biotic and abiotic stresses, including osmotic pressure regulation and optimization of photosynthesis.